Homochirality in space – Selective enrichment of chiral molecules on chiral surfaces - Marloie G.; Pauzat F.; Ellinger Y.; Markovits A.; Pilmé J. (BIO Web of Conferences, 2014)
Life on Earth, as we know it to day, is inseparable from homochirality. The presence of an enantiomeric excess in carbonaceous chondrites is well documented; among the different hypotheses considered to explain this undisputed fact, we chose to investigate the possibilities open by a selective adsorption on a chiral surface that would engage a process of enantiomeric enrichment. The chiral surface is that of the α-quartz { 10 10¯ } $\left\{ {10\,\overline {10} } \right\}$ and the chiral molécule is lactic acid, HOCH(CH3)COOH. In this theoretical work we rely on numerical simulations based on Density Functional Theory (DFT) that proved efficient in the super-molecule and periodic approaches to this category of phenomena. In view of the different types of adsorption sites, a statistical treatment was necessary; it shows that (S)-lactic acid is preferentially adsorbed with a selectivity of ~0.7 kcal/mol with respect to the (R) isomer.